2019
DOI: 10.1101/800722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between breastfeeding and DNA methylation over the life course: findings from the Avon Longitudinal Study of Parents and Children (ALSPAC)

Abstract: BackgroundBreastfeeding is associated with short and long-term health benefits. Long-term effects might be mediated by epigenetic mechanisms, yet a recent systematic review indicated that the literature on this topic is scarce. We performed the first epigenome-wide association study of infant feeding, comparing breastfed vs non-breastfed children. We measured DNA methylation in children from peripheral blood collected in childhood (age 7, N=640) and adolescence (age 15-17, N=709) within the Accessible Resource… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…Ideally, future studies should meta-analyse data from multiple cohorts in order to avoid their studies being hindered by low power and sample size. Indeed, recently, two Epigenome-Wide Association Studies have been conducted in children from buccal cells collected around age nine [51] and peripheral blood cells at ages 7 and 15-17 [52]. Both studies reported some evidence for the association of breastfeeding with offspring DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, future studies should meta-analyse data from multiple cohorts in order to avoid their studies being hindered by low power and sample size. Indeed, recently, two Epigenome-Wide Association Studies have been conducted in children from buccal cells collected around age nine [51] and peripheral blood cells at ages 7 and 15-17 [52]. Both studies reported some evidence for the association of breastfeeding with offspring DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up analyses were done for CpGs that were previously associated with breastfeeding in EWASs or candidate gene studies. These included all CpGs on the EPIC array that were annotated to the genes LEP ( n CpGs = 23) [52,53,54,55,58], IL4R ( n CpGs = 37) [58], CDKN2A ( n CpGs = 32) [59], 1 CpG from the study of Hartwig et al [60], and 4297 suggestive CpGs from the study of Naumova et al [53]. In total, this resulted in a list of 4370 CpGs, of which 3859 CpGs were present (after QC) in our data.…”
Section: Methodsmentioning
confidence: 99%
“…Not having been breastfed has been associated with an increase in methylation of the promoter of the tumor suppressor gene CDKN2A (cyclin dependent kinase inhibitor 2A) in premenopausal breast tumors of 639 women (mean age of 57.6 years) [59]. In a more recent EWAS study, breastfeeding (dichotomized as never vs. ever) was associated with changes in the TTC34 gene at age 7 ( n = 640), which were still evident in adolescence ( n = 709) [60]. These previous epigenetic studies of breastfeeding were often conducted with relatively small samples (average sample size = 307, range = 37–640).…”
Section: Introductionmentioning
confidence: 99%
“…Um estudo recente fornece evidências sobre a magnitude e persistência da associação entre amamentação e metilação do DNA 71 . Os achados dos autores sugerem que a amamentação estava associada às alterações no perfil da metilação do DNA de indivíduos aos 7 e 15-17 anos de idade 71 72 também encontrou associação entre a duração da amamentação e a metilação da leptina aos 10 anos de idade e também às trajetórias do Índice de Massa Corporal (IMC). A leptina é um hormônio relacionado à saciedade e pode ser um dos mecanismos plausíveis para explicar a relação inversa entre amamentação e obesidade 23 .…”
Section: P á G I N a | 24unclassified